Printing of covalent organic frameworks using multi-material in-air coalescence inkjet printing technique. Issue 36 (27th August 2021) - Teo, Mei Ying; Kee, Seyoung; Stuart, Logan; Stringer, Jonathan; Aw, Kean C.
Abstract : Multi-material in-air coalescence inkjet printing technique and the patterned COF using this printing method. Abstract : In this work, we have demonstrated the creation of monolithic covalent organic frameworks (COFs) through the use of in-air coalescence and reaction of inkjet printed monomer droplets. This method circumvents issues that would reduce printability of the COF using conventional inkjet printing approaches, and shows excellent consistency and spatial uniformity of the fabricated COF.